Effects of the COVID-19 pandemic on healthcare utilization among older adults with cardiovascular diseases and multimorbidity in Indonesia: an interrupted time-series analysis - Royasia Viki Ramadani; Mikael Svensson; Sven Hassler; Budi Hidayat; Nawi Ng (BMC Public Health, 2024)
Abstract Background The COVID-19 pandemic has disrupted healthcare utilization globally, but little is known about the effects among patients with cardiovascular diseases (CVDs) and other multimorbidities. This study analyzed the impacts of COVID-19 on healthcare utilization for patients aged 30 years and older with cardiovascular diseases (CVDs) with or without other chronic disease comorbidities in Indonesia. Methods We designed a retrospective cohort study based on the Indonesian National Health Insurance (NHI) sample data from 2016–2020. We defined healthcare utilization as monthly outpatient and inpatient visits related to chronic diseases at the hospital and primary healthcare levels per 10,000 NHI members. We used interrupted time series analysis to evaluate how the healthcare utilization patterns had changed due to the COVID-19 pandemic. Results Overall, hospital outpatient visits decreased by 39% when the pandemic occurred (95% Confidence Interval (CI): 0.48,0.76), inpatient visits by 28% (95% CI: 0.62,0.83), and primary healthcare visits by 34% (95% CI:0.55, 0.81). For patients with CVDs and multimorbidity, hospital outpatient and inpatient visit rates were reduced by 36% and 38%, respectively and primary healthcare visits by 32%. Some insignificant differences in the reduction of out-and inpatient visits were observed across diagnosis groups and regions. Conclusion Healthcare utilization among patients with chronic diseases decreased significantly during COVID-19 and consistently across different chronic diseases and regions. To cope with the unmet needs of healthcare utilization in the context of the pandemic, the healthcare system needs to be strengthened to cater to the needs of the population-at-risk, especially for patients with CVDs and multimorbidity.